Optimization of Spectral Efficiency in Massive MIMO Network for Different Deployment Scenarios - Kausar, Raabia; Gupta, Akhil (International Journal of Sensors Wireless Communications and Control, 2021)
Background: Spectrum efficiency is labelled to be the most discussed area of wireless communication. Today, wireless communication is one of the fastest developing fields due to which there is a tremendous increase in subscribers that leads to the demand for more spectrum. Though the growth in the spectrum is not possible but optimizing it is a good alternative. Methods: This paper provides a detailed study of different methods used for the optimization of spectrum efficiency in massive multiple inputs and outputs. The main goal of this paper is to findout how the spectrum could be used efficiently to meet user demands. It includes the technique of fixing specific parameters like coherent block length, number of reception antennas, pilots reuse factor, signal to noise ratio, and number of users to make more efficient use of the spectrum. This paper also explains the achievement of spectral efficiency under different deployment scenarios i.e., urban, suburban, and rural in ITU-R M.2135 standard. Results: As seen from the results, steep SEs are accomplished by making a schedule of many UE for mutual broadcast, while the SE per UE maybe 1-4 bit/s/Hz. These high-class demonstrations show that massive MIMO e.g an SNR of 0-5 dB with a limited pilot reuse factor of β= 3, and the fast techniques are applied for lessening the distortion noise and instrument damage. According to the simulations, it is found that massive MIMO with M = 100 can produce a 10×gain in SE in the IMT-Advanced requirements of 3 bit/s/Hz/cell. For the bigger sizes of antennas, M = 500 massive MIMO can even give 40×gain over IMT-Advanced. Conclusion: With the advancement of technology, the number of users is increasing tremendously, leading to a shortage of spectrum. Hence, the need of the hour is to make efficient use of the available spectrum while maintaining the Quality of service. Therefore, researchers have proposed specific methods that fulfill this need. The paper realizes the SE approach on different deployment scenarios like urban, suburban and rural in the ITU-R M.2135 standard and proves that under all the three scenarios, P-ZF remained unchanged. As seen from the results, steep SEs are accomplished by making a schedule of many UE for mutual broadcast, while the SE per UE maybe 1-4 bit/s/Hz. These high-class demonstrations show that massive MIMO likes an SNR of 0–5 dB with a limited pilot reuse factor of β= 3, and the fast techniques are applied for lessening the distortion noise from instrument damage. According to the simulations, it is seen that massive MIMO with M = 100 can produce a 10×gain in SE in the IMT-Advanced requirements of 3 bit/s/Hz/cell. For the bigger sizes of antennas, M = 500 massive MIMO can even give 40×gain over IMT-Advanced. The outcomes in this paper suggest the uncorrelated fading, although for decreasing inter-user interference, correlated fading is required, to raise large SE with less β. This study makes SE independent of topography. Furthermore, optimization of energy under different deployment scenarios, along with these simulations, can optimize the spectrum to a greater extent.
Keywords: quality of service